The Association between Aromatase Gene Polymorphism Cyp19 Val 80 and Endometriosis Risk - Syifa Alkaf; Ziske Maritska; Venny Patricia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Endometriosis implant has been known to express aromatase enzyme, Cytochrome p450 that catalyzes androgen into estrogen. It causes local estrogen production, leading to increased estrogen level, and subsequently triggers endometriosis lesion. CYP19 gene resided at chromosome 15q21.1 is the biggest component of aromatase coding cytochrome p450 enzyme. Objective: To identify relationship between aromatase gene polymorphism CYP19 Val 80 and the risk of endometriosis. Methods: This is an observational case-control study using frozen DNA sample from women with endometriosis and/ or adenomyosis who had undergone laparotomy/ laparoscopy at Obstetrics and Gynecology Department Dr. Mohammad Hoesin General Hospital Palembang January-November 2013. Samples were amplified and cut by PCR-FRLP using Rsa1 restriction enzyme. Results were divided into A/A genotype (homozygote mutant), G/A (heterozygote mutant), and G/G (homozygote wild type). Data were analyzed by SPSS 21.0 version. Results: PCR-RFLP results for A/A genotype were 20 (21.3%) in endometriosis group and 8 (8.5%) in control group. G/A genotype were 18 (19.1%) in endometriosis group and 22 (23.4%) in control group. G/G genotype were 9 (9.6%) and 17 (18.1%) in endometriosis group and control group, respectively. There was significant increase risk of endometriosis in women carrying genotype A/A to those with genotype G/G with OR 4.722 (p<0.05). Conclusion: Polymorphism on aromatase gene CYP19 Val 80 A/A increases risk of endometriosis.